Post-treatment with Telfairia occidentalis seed oil attenuates alcohol-induced testicular damage in Sprague-Dawley rats - Ademola Ayodele Oremosu; Edidiong Nnamso Akang; Catherine Chukwumuanya Adigwe; Iniebehe Essien Okoko; Onyemaechi Okpara Azu3 (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2013)
Background: Long term alcohol use has been implicated in men with sexual disorders including suppression of testosterone levels as well as testicular morphological changes. Objective: This research investigated the ability of Telfairia occidentalis (T.O.) to attenuate the damaging effects of alcohol on the testicular parameters. Materials and Methods: Thirty male Sprague-Dawley rats, 170-190 grams were divided into 6 groups, A to F and treated with distilled water (DW) for the period of 8 weeks (positive control group A), ethanol for 2 weeks followed with DW for 6 weeks (group B) (negative control), ethanol alone for 2 weeks (group C) while others received ethanol for 2 weeks, followed with 200 (group D), 400 (group E) and 600 mg/kg (group F) of T.O. for 6 weeks. Results: Testicular histological sections showed that ethanol produced marked loss of testicular germ cells after two weeks of administration. T.O (200 mg/kg body weight) was not able to attenuate this microanatomical distortion when compared with control groups, but at 400 mg/kg body weight, T.O reversed the ethanol`s effects with resultant significant increase in sperm count and motility (p<0.05), serum testosterone levels (p<0.05), and testicular weight (p<0.05). However, at 600 mg/kg dosage, there was marked depletion of testicular germ cells with atrophied seminiferous tubules and a decrease in semen parameters and testicular weight. Conclusion: Our result suggests that T.O promotes the regeneration of testicular germ cells and improves semen quality at a certain critical dose. Hence, T.O has a potential of reversing ethanol induced testicular damage.